Aechmea nigribracteata (Bromeliaceae), a new species from southern Bahia, Brazil - Maciel, Jefferson Rodrigues; Louzada, Rafael; Alves, Marccus (Phytotaxa, 2014)
Herein is described and illustrated a new Aechmea species. Aechmea nigribracteata grows in southern Bahia (Brazil), a region recognised as highly diverse in bromeliads. Aechmea nigribracteata belongs to Aechmea subg. Chevaliera and has completely dentate, blackish floral bracts and petals with two crenate-laciniate ligules.